Harmonisasi Hukum Ekonomi dalam Mewujudkan Kemakmuran Masyarakat Indonesia - Farida Sekti Pahlevi (ACTIVA: Jurnal Ekonomi Syariah, 2019)
The Indonesian state has a responsibility in ensuring the prosperity of its citizens in accordance with the ideals of the nation as contained in Pancasila and the 1945 Constitution. Equitable welfare can be created when equality of economic, political, socio-cultural rights, equal treatment before the law is well implemented, constitution expressly mandates that social welfare is the highest priority of Indonesia's public policy. The reciprocal relationship between law and economics is a reference in fulfilling the needs of the community. The Pancasila economic system is the Indonesian economic system which in its implementation always adheres to the national personality. Economic activities involving the interests of many people are needed by the Law so that every problem that occurs can be resolved in accordance with the applicable rules. Economic activities in society must always move, develop and order according to the needs of the community in a country. Economic law by realizing the prosperity of the people of Indonesia needs to be harmonized. The development of economic activities that are relatively more rapid so far, needs to be followed by the development of legal arrangements, so that people's prosperity can be realized in accordance with the hopes and ideals of the nation. Basically the study of economic law is directed at increasing the carrying capacity of legislation that regulates economic activities. The complete set of laws or legislation will provide legal certainty for the implementation of legal relations that create rights and obligations for legal subjects, in general, as well as in the relations of economic activities in particular